PENGUKURAN RADIOAKTIVITAS GAMMA PADA SAMPEL TANAH DI DAERAH KABUPATEN MAMUJU - Imran, Dzulqadri; Iswadi, Iswadi; Zelviani, Sri; Supriyatni, Elisabeth (JFT: Jurnal Fisika dan Terapannya, 2019)
The research aims to determine the level of radioactivity in the district of Mamuju and compare it with other land activities. and prove previous research on land activity in Mamuju is quite high. Measurements are done using the method of counting and identifying. That is identifying the radionuclides contained in the sample according to the Uranium and Thorium series. The tools used are LBC (Low Background Counter) and Gamma spectrometry. The results showed that: land activity in all samples has exceeded the limits established by PERKA BAPETEN and IAEA (International of Atomic Agency). The highest radioactivity results are found in the Takandeang region. And on all three samples showed the results of a very significant natural radionulida activity on vulnerable concentrations of activity in European countries.